PENGGUNAAN NILAI-NILAI DISKRIMINAN ALTMAN UNTUK MENGUKUR KINERJA KEUANGAN PT. FAVO STAR FASTINDO GARMENTS TAHUN 2002 - 2004 - Ismulyana Djan; Nasai . (STIE Binaniaga, 2006)
The research used quantitative descriptive method by emphasizing case study, the purpose of the research was to get the clear and wide picture of the problem in the hope that the writer can set up the relationship and trend of the phenomenon when the research was being done. The method the writer used in analyzing the financial performance of PT. Favo Star Fastindo Garments is Z-Score (Multivariance Discriminant Analysis) created by Prof. Edward I Altman from New York University. The mathematical equation of the Z-Score = 1.717 X I + 0.847 X2 + 3.107 X3 + 0.420 X4 + 0.998 X5. Based on the general analysis from 2002 to 2004 and trend for 2005, it can be concluded that the financial performance of PT. Favo Star Fastindo Garments was categorized as “healthy” with declining efficiency. This was proved by all the Z-Scores that lower than healthy standard Z-Score from Altman. However, in time detailed analysis the ZScores tend to decrease, caused by discriminant values from 2002 – 2004 that tend to decrease, even in 2005 trend analysis the discriminant value was 3 X 3, that is smaller than standard healthy value from Altman. This was a warning for the management to instantly conduct improvement action, if not in the coming years other discriminant values may be fall which automatically the Z-Score also falls and eventually lead to the company’s bankruptcy